PERGULATAN PENDIDIKAN AGAMA ISLAM DI KAWASAN MINORITAS MUSLIM - Wahib, Abdul (IAIN Walisongo Semarang, 2011)
Abstract Â This study was conducted with a qualitative approach. Data obtained by in-depth interviews, observation and documentation. Data were analyzed by phenomenological qualitative analysis model. This study concluded: (1) about the life of the Muslim minority in the school before and after the bombing; With imitate the concept of immersion, the good relations established between the Hindu-Muslim, but the bombs are up to two times it has damaged the relationship patterns that have progress, (2) the internal problems of PAI Teachers: The teachers of Islamic religious education in Bali faced a different problem that encompasses many domains of life. In school /classroom, in social life and so on, (3) materials additional Islamic Education, also called local curriculum include: Instilling a sense of respect for people who embrace different beliefs. Â *** Kajian ini merupakan kajian dengan pendekatan kualitatif. Data penelitian diperoleh dengan wawancara mendalam, observasi, dan dokumentasi. Data dianalisis dengan analisis fenomenologi. Kesimpulan dari kajian ini adalah: (1) terkait dengan kehidupan minoritas muslim disekolah sebelum dan sesudah peristiwa peledakan bom:hubungan yang semula baik kemudian menjadi rusak; (2) problem internal guru-guru PAI: Guru-guru PAI di Bali menghadapi masalah yang rentangnya sangat beragam terkait dengan wilayah kehidupan: sekolah, ruang kelas, dan kehidupan sosial; (3) bahan dalam kurikulum lokal: perlu dimasukkannya materi tentang penghormatan terhadap penganut keyakinan yang berbeda. Â Keywords: Pendidikan Agama Islam, minoritas, survive